A magyarság helyzete a Román-Bánságban a két világháború között = Situation of Hungarians in Romanian Banat between the two world wars - Kókai, Sándor (Közép-Európai Közlemények, 2018)
With the Treaty of Trianon, it was only internationally legally described with Hungary what was actually happened in Banat in November 1918 in a few weeks. In the wake of the Padovan cease-fire for closing the military events of the First World War as well as the military convention of Belgrade, the Serbian and Romanian troops could advance unhindered, and the new state power came in behind them, which quickly and systematically settled in Banat. For the smooth completion of occupation and conscious separation, the assistance was provided by the French, whose impartiality only we hoped for, and whose bitter disappointments were quickly experienced by the Hungarians of Banat, too. The result: Serbia received 938 km2 (193 settlements) from the area of Torontál and Temes County, as well as two settlements with 23 km2 area from Krassó-Szörény County. Nearly two thirds of the Banat (66.1% = 18848 km2, 599 settlements) were given to Romania by diplomatic maneuvers: no referendum was held anywhere in the disputed areas. The unification of Hungarians did not happen in the past 100 years. The Hungarian spiritual and cultural values of Banat and also the wherewithal have the last days of their living and are practically disappearing from this region.